Phytocompounds of Nigella sativa seeds extract and their neuroprotective potential via EGR1 receptor inhibition: A molecular docking study - Kulsum, Kulsum; Syahrul, Syahrul; Hasbalah, Kartini; Balqis, Ummu (Narra J, 2023)
Bioactivity of Nigella sativa seed extract has the potential as a neuro-protector, offering its promising utility in the clinical setting for brain injury management. This study aimed to identify the phytocompounds contained in the extract of N. sativa seeds and further screen their respective neuronal anti-inflammatory activities in silico. The extract of N. sativa seeds was prepared through successive maceration using non-polar to polar solvents (n-hexane and ethanol, respectively). The phytocompounds in the ethanolic extract were initially identified through qualitative analysis and further analyzed with gas chromatography-mass spectrometry (GC-MS). The spectral data were compared with the compound library for identification. The identified phytocompounds were then simulated computationally for their binding affinities toward the active pocket of early growth response-1 (EGR1) receptor (PDB: 14r2a). We found that the ethanolic extract of N. sativa seeds were predominantly constituted of hexadecanoic acid, ethyl ester (17.15%); linoleic acid ethyl ester (15.0%); octadecanoic acid (13.26%); and ethyl oleate (10.38%). The binding affinity of the phytocompounds ranged from -7.49 kcal/mol (methyl palmitoleate) to -14.31 kcal/mol (9-hexadecanoic acid, methyl ester), with 12 compounds having binding affinity < -10 kcal/mol. In conclusion, ethanolic extract of N. sativa seeds are rich with fatty acids that have active as anti-inflammatory and may exert neuronal protection by inhibiting EGR1 receptor. Studies using animal models to confirm the activity are warranted.